1982
DOI: 10.1017/s0007485300010579
|View full text |Cite
|
Sign up to set email alerts
|

Active and resting behaviour of virgin and pregnant females ofGlossina morsitans morsitansWestwood (Diptera: Glossinidae) in the laboratory

Abstract: Activity in virgin and pregnant females of Glossina morsitans morsitans Westw. was very low and mostly took the form of short bursts of flight. Recently-fed virgins and females in early and mid-pregnancy were least active. In late pregnancy, activity increased and more walking occurred. In all classes of females, activity was least around midday, but the V-shaped curve became less pronounced as parturition approached. There was evidence of a slight preference for black over white surfaces when landing but a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Finally, the lack of visual responsiveness before and around larviposition suggests that the contemporary inactivity (Brady & Gibson, 1983) and photonegativity (Rowcliffe & Finlayson, 1982) go hand-in-hand with a general unarousability, which is likely t o lead t o a strong tendency for pregnant females to stay put in dark shelters, and thus avoid exposure t o ULV insecticide applicationsa further reason for their unusual ability t o survive such sprays (Davies, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the lack of visual responsiveness before and around larviposition suggests that the contemporary inactivity (Brady & Gibson, 1983) and photonegativity (Rowcliffe & Finlayson, 1982) go hand-in-hand with a general unarousability, which is likely t o lead t o a strong tendency for pregnant females to stay put in dark shelters, and thus avoid exposure t o ULV insecticide applicationsa further reason for their unusual ability t o survive such sprays (Davies, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Not only d o they become almost totally immobile for some 4 8 h before depositing a larva, but their circadian rhythm is also much modified: 2 days before larviposition the morning peak of their typical V-shaped flight pattern is over twice as high as normal; virtually no activity occurs for the whole of the day preceding larviposition; and on the day of larviposition, whereas the morning peak of the V is still heavily suppressed, there then occurs a wholly untypical period of high activity in the early afternoon just preceding parturition. Brady & Gibson (1983) postulated that, by preventing heavily pregnant females from flying out into insecticide clouds, this 48 h of inactivity, associated with such females' concurrent photonegativity (Rowcliffe & Finlayson, 1982) might be one reason for the fact that pregnant females are the only members of G.morsitans populations t o survive aerosol non-residual insecticide campaigns (Davies, 1978). The other and perhaps principal reason is that any insecticide picked u p by pregnant females tends to be shunted to the larva via the female's highly lipid 'milk' (see Kwan et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The clumping of puparia within cavities, beneath objects such as rock overhangs or fallen logs, or in dense thickets, is widely recognized. Pregnant females become intensely active a few hours before parturition (Rowcliffe & Finlayson, 1982;Brady & Gibson, 1983;Denlinger et al 1983), and it is presumably during this time that the female seeks the parturition site. Laboratory experiments suggest a long distance attraction by pregnant females to a dark solid profile and a close range attraction to a shaded region, especially a horizontally orientated shading surface (Rowcliffe & Finlayson, 1981).…”
Section: Site Selectionmentioning
confidence: 99%
“…These experiments were all conducted at a constant temperature of 25, 26 or 27°C. Only Rowcliffe & Finlayson (1981, 1982 Correspondence: Professor L. H. Finlayson have investigated the effects of temperature fluctuations on the behaviour of late pregnancy tsetse flies. They demonstrated that as pregnancy progressed there was an increasing tendency to rest in darker sites and that this photonegative response increased with temperature, thus indicating a search for cooler shaded areas.…”
Section: Introductionmentioning
confidence: 99%
“…The aim was to recreate the situation in the field in which the gravid female is subjected to a sudden rise in temperature, as, for example, when she moves from shade to full sun, or when she alights on hot soil. Apart from orientation responses (Rowcliffe & Finlayson, 1981, 1982 is there any effect on the larviposition behaviour of the fly?…”
Section: Introductionmentioning
confidence: 99%